Carboxylic acid rare earth complex, composite material and preparation method and application thereof

By combining carboxylic acid rare earth complex with silane coupling agent with silica, a composite material was prepared, which solved the problems of complex operation, high cost and insufficient detection sensitivity of existing PCBs detection methods, and achieved high sensitivity detection and good stability of PCBs.

CN119822954AActive Publication Date: 2025-04-15BAOTOU RESEARCH INSTITUTE OF RARE EARTHS +1

Patent Information

Application Number
CN202510029789.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-08
Publication Date
2025-04-15
Estimated Expiration
2045-01-08

AI Technical Summary

Technical Problem

The existing PCBs detection methods have complex operation, high cost and insufficient detection sensitivity, which are difficult to meet the demand for PCBs detection.

Method used

By combining the carboxylic acid rare earth complex with silane coupling agent with silica, a composite material is prepared that can detect PCBs highly sensitively.

Benefits of technology

Sensitive detection of PCBs is achieved, with a detection detection limit of up to 12 μM, and the composite material has good stability and recyclability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119822954A_ABST
    Figure CN119822954A_ABST
Patent Text Reader

Abstract

The invention discloses a carboxylic acid rare earth complex, a composite material and a preparation method and application thereof. The carboxylic acid rare earth complex is formed by complexing carboxylic acid shown in the formula (I) and rare earth elements. The composite material prepared by combining the carboxylic acid rare earth complex with a silane coupling agent and silicon dioxide can sensitively detect polychlorinated biphenyl. # imgabs0 #
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a carboxylic acid rare earth complex, a composite material and a preparation method and application thereof. Background Art

[0002] Polychlorinated biphenyls (PCBs) are chlorinated biphenyl compounds formed when hydrogen atoms on biphenyl are replaced by different numbers of chlorine atoms. Due to its stable physical and chemical properties, it is widely used as insulating oil, heat carrier and lubricating oil, etc. It can also be used as an additive for various industrial products (such as resin, rubber, binder, coating, carbon paper, ceramic glaze, fire retardant, pesticide delay agent, dye dispersant). PCBs are widely present in the atmosphere, soil, water and other environments, and can be enriched in organisms through the food chain. Because PCBs are toxic and carcinogenic, they pose a huge threat to biological health. Therefore, it is extremely important to monitor and control PCBs in the environment.

[0003] At present, PCBs detection is mostly carried out using detection instruments. However, most detection instruments are relatively expensive and require professional personnel to make them, with complex processes and high costs, and the detection sensitivity needs to be improved. Therefore, it is of great significance to develop a PCBs detection method that is simple to operate and highly sensitive.

[0004] Due to their unique 4f electron layer structure, rare earth elements exhibit rich separation energy levels and long-lived excited states, and have very strong absorption and transfer capabilities for radiation. Therefore, rare earth elements can be used as various spectral luminescent materials and laser materials. Rare earth complexes have the advantages of narrow spectral band, high color purity, and stable physical and chemical properties, and are often used as fluorescent probe materials. The luminescence principle of rare earth complexes is that organic ligands absorb energy, and then transfer energy to rare earth ions through intramolecular energy transfer, causing them to sensitize and emit light. This method is called the "antenna effect."

[0005] CN106432295A discloses a method for 3+ A sensitized luminescent metal organic framework. The luminescent metal organic framework is prepared by a solvent thermal method using a cadmium salt and a 2,5-di-(3,5-dicarboxyphenyl)thiophene dicarboxamide (H4L) ligand. The luminescent metal organic framework itself does not contain rare earth elements and is used for sensitizing rare earth elements.

[0006] CN106190103A discloses a lipophilic silica rare earth nano fluorescent material. The fluorescent material is prepared by using alkyl / carboxyl modified nano silica as a ligand, adding organic small molecules as co-ligands, and coordinating with rare earth ions in an organic solvent; the alkyl / carboxyl modified nano silica is prepared by modifying nano silica with an amino silane coupling agent and an alkyl silane coupling agent, and further reacting with aromatic carboxylic acid or its derivatives. The lipophilic silica rare earth nano fluorescent material is mainly used for fluorescent anti-counterfeiting ink.

[0007] CN101735216A discloses a europium complex silicon dioxide fluorescent nanoparticle. The fluorescent nanoparticle uses a europium rare earth fluorescent complex as a core, and silicon dioxide with amino groups on the surface is wrapped around the complex to form a core-shell fluorescent nanoparticle. The fluorescent nanoparticle uses 4,7-diphenyl-1,10-phenanthroline-2,9-dicarboxylic acid as a ligand, and silicon dioxide is wrapped around the complex to form a core-shell structure, which easily causes uneven particles and agglomeration.

[0008] Existing rare earth complexes often have disadvantages such as large blocks and easy agglomeration, which affects their stability in application. Summary of the invention

[0009] In view of this, one object of the present invention is to provide a carboxylic acid rare earth complex, which is combined with a silane coupling agent and silicon dioxide. The detection limit of the prepared composite material for polychlorinated biphenyls is at most 12μM, and it can be used to sensitively detect polychlorinated biphenyls. Another object of the present invention is to provide a method for preparing the above-mentioned carboxylic acid rare earth complex. Another object of the present invention is to provide a composite material. Another object of the present invention is to provide a method for preparing the above-mentioned composite material. Another object of the present invention is to provide a use of the above-mentioned composite material.

[0010] The present invention adopts the following technical solutions to achieve the above-mentioned purpose.

[0011] In one aspect, the present invention provides a carboxylic acid rare earth complex, which is formed by complexing carboxylic acid with rare earth element ions; wherein:

[0012] The carboxylic acid has a structure as shown in formula (I):

[0013]

[0014] Wherein, R1, R2, R3, and R4 are independently selected from hydrogen or a C1-C6 alkyl group.

[0015] According to the carboxylic acid rare earth complex of the present invention, preferably, the rare earth element ion is selected from La 3+ 、Ce 3+ 、Sm3 + 、Eu 3+ , Gd 3+ , Tb 3+ 、Dy 3+ , Y 3+ At least one of .

[0016] According to the carboxylic acid rare earth complex of the present invention, preferably, the carboxylic acid rare earth complex is obtained by reacting a carboxylic acid represented by formula (I) and a compound containing a rare earth element; wherein the molar ratio of the carboxylic acid represented by formula (I) to the rare earth element in the compound containing the rare earth element is 1:(1-6).

[0017] On the other hand, the present invention also provides a method for preparing the above-mentioned carboxylic acid rare earth complex, comprising the following steps:

[0018] The carboxylic acid represented by formula (I) is reacted with a compound containing a rare earth element in a solvent under acidic conditions to obtain a carboxylic acid rare earth complex;

[0019] Wherein, the compound containing rare earth elements is selected from at least one of oxides of rare earth elements and inorganic salts of rare earth elements;

[0020] The solvent includes solvent A and solvent B; the solvent A is selected from at least one of acetonitrile, tetrahydrofuran, dimethylformamide, dimethylacetamide, and dimethyl sulfoxide; the solvent B is selected from at least one of water and C1-C5 alkyl alcohol;

[0021] The reaction temperature is 80-150°C.

[0022] According to the preparation method of the present invention, preferably, the preparation method of the carboxylic acid represented by formula (I) comprises the following steps:

[0023] 1) adding titanium chloride, a reducing agent, and a compound represented by formula (II) into a first solvent and mixing them, so that the compound represented by formula (II) undergoes a McMurry coupling reaction to obtain an intermediate product A;

[0024]

[0025] Wherein, R1 and R2 are independently selected from hydrogen or C1-C6 alkyl; R5 and R6 are independently selected from C1-C6 alkyl;

[0026] The first solvent is selected from at least one of acetonitrile, tetrahydrofuran, dimethylformamide, dimethylacetamide, and dimethyl sulfoxide;

[0027] 2) adding the intermediate product A and the boron halide into a second solvent for reaction to obtain an intermediate product B;

[0028] The second solvent is selected from at least one of halogenated alkanes;

[0029] 3) adding an alkali metal alkoxide to a third solvent for a first reaction; then adding the intermediate product B for a second reaction; then adding the compound represented by formula (III) for a third reaction to obtain an intermediate product C;

[0030]

[0031] Wherein, R3 and R4 are independently selected from hydrogen or C1-C6 alkyl; R7 is selected from C1-C6 alkyl; X1 is halogen;

[0032] The third solvent is selected from at least one of acetonitrile, tetrahydrofuran, dimethylformamide, dimethylacetamide, and dimethyl sulfoxide;

[0033] 4) adding an alkali metal hydroxide and the intermediate product C into a fourth solvent for reaction, removing the organic solvent after the reaction, and adding an acid to obtain a carboxylic acid represented by formula (I);

[0034] The fourth solvent includes solvent C, solvent D and solvent E; the solvent C is selected from at least one of acetonitrile, tetrahydrofuran, dimethylformamide, dimethylacetamide, and dimethyl sulfoxide; the solvent D is selected from at least one of C1-C5 alkyl alcohols; and the solvent E is water.

[0035] In another aspect, the present invention further provides a composite material, wherein the composite material is formed by coating the above-mentioned carboxylic acid rare earth complex on the surface of silicon dioxide via a silane coupling agent.

[0036] According to the composite material of the present invention, preferably, the silane coupling agent is selected from at least one of N-(β-aminoethyl-γ-aminopropyl)methyldimethoxysilane, N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane, γ-aminopropyltriethoxysilane, γ-aminopropyltrimethoxysilane, vinyltrimethoxysilane, γ-(2,3-epoxypropyloxy)propyltrimethoxysilane, γ-(methacryloyloxy)propyltrimethoxysilane and γ-mercaptopropyltriethoxysilane.

[0037] In another aspect, the present invention further provides a method for preparing the composite material, comprising the following steps:

[0038] A) immersing the silicon dioxide in a weak alkaline aqueous solution and allowing it to stand for 1 to 12 hours, followed by filtering, washing and drying the silicon dioxide; wherein the weak alkaline aqueous solution is selected from at least one of aqueous ammonia, an aqueous solution of an alkali metal carbonate, and an aqueous solution of an alkali metal bicarbonate;

[0039] B) placing the dried silica and silane coupling agent in step A) in a C1-C5 alkyl alcohol and reacting at 50-120° C. to obtain silica with the surface coated with the silane coupling agent;

[0040] C) placing the silicon dioxide with the surface coated with a silane coupling agent obtained in step B) and the carboxylic acid rare earth complex according to any one of claims 1 to 3 in a C1 to C5 alkyl alcohol and reacting them at 50 to 120° C. to obtain a composite material.

[0041] According to the preparation method of the present invention, preferably, in step C), the reaction is carried out at a pH value of 6 to 8.

[0042] In another aspect, the present invention also provides use of the composite material in detecting polychlorinated biphenyls.

[0043] The present invention forms a carboxylic acid rare earth complex by complexing a polycarboxylic acid shown in formula (I) with a rare earth element. The coordination bond formed by the polycarboxylic acid shown in formula (I) and the rare earth center is very strong, and the coordination mode is diverse, so a variety of carboxylic acid rare earth complexes with large pores and multidimensional structures can be synthesized. The composite material prepared by combining the carboxylic acid rare earth complex with a silane coupling agent and silicon dioxide has a detection limit of at most 12 μM for polychlorinated biphenyls, and can be used for sensitive detection of polychlorinated biphenyls. At the same time, the prepared composite material has good stability and recyclability. BRIEF DESCRIPTION OF THE DRAWINGS

[0044] Figure 1 This is the preparation route of tetrakis-(4-carboxy-1-methyleneoxy-(1,1-biphenyl))ethylene (H4L) in Preparation Example 1.

[0045] Figure 2 This is the preparation route of the composite material (SiO2@WD-53@L-Eu) in Example 1.

[0046] Figure 3 This is the XPS spectrum of the composite material SiO2@WD-53@L-Eu in Experimental Example 1; where a is the total spectrum, b is the C1s spectrum, c is the O1s spectrum, and d is the Eu3d spectrum.

[0047] Figure 4 TEM images of the composite material SiO2@WD-53@L-Eu in Experimental Example 1 at different magnifications; wherein, a is a TEM image at a 500nm scale, b is a TEM image at a 100nm scale, c is a TEM image at a 50nm scale, and d is a schematic diagram of the core-shell structure of the TEM image at a 50nm scale.

[0048] Figure 5This is the TEM element mapping image of the composite material SiO2@WD-53@L-Eu in Experimental Example 1 at a scale of 80 nm; wherein, e is the mapping image of the composite material SiO2@WD-53@L-Eu, f is the mapping image of the element Si, g is the mapping image of the element O, h is the mapping image of the element C, i is the mapping image of the element N, and j is the mapping image of the element Eu.

[0049] Figure 6 This is the infrared spectrum of Experimental Example 1.

[0050] Figure 7 This is the fluorescence spectrum of the composite material SiO2@WD-53@L-Eu after adding different amounts of 2,2',5-trichlorobiphenyl solution in Experimental Example 2.

[0051] Figure 8 This is the fluorescence spectrum of the composite material SiO2@WD-53@L-Eu after adding different amounts of 2,2',5,5'-tetrachlorobiphenyl solution in Experimental Example 2.

[0052] Fig. 9 This is the fluorescence spectrum of the composite material SiO2@WD-53@L-Eu after adding different amounts of 2,2',4,4',5,5'-hexachlorobiphenyl solution in Experimental Example 2.

[0053] Fig.10 It is the fluorescence intensity of the composite material SiO2@WD-53@L-Eu in Experimental Example 3 at an emission wavelength of 616 nm in four fluorescence quenching experiments. DETAILED DESCRIPTION

[0054] The present invention is further described below in conjunction with specific embodiments, but the protection scope of the present invention is not limited thereto.

[0055] <Carboxylic acid rare earth complex>

[0056] The carboxylic acid rare earth complex provided by the present invention is formed by complexing carboxylic acid with rare earth element ions; wherein,

[0057] The carboxylic acid has a structure as shown in formula (I):

[0058]

[0059] In formula (I), R1, R2, R3, and R4 can be independently selected from hydrogen or C1-C6 alkyl, preferably hydrogen or C1-C3 alkyl, more preferably hydrogen or C1-C3 n-alkyl. Most preferably, R1, R2, R3, and R4 are all hydrogen.

[0060] According to a specific embodiment of the present invention, the carboxylic acid represented by formula (I) has the structure shown below:

[0061]

[0062] In the present invention, the C1-C6 alkyl group may include, but is not limited to, methyl, ethyl, propyl, isopropyl, butyl, isobutyl, sec-butyl, tert-butyl, pentyl, methylbutyl, ethylpropyl, hexyl, methylpentyl, dimethylbutyl, and ethylbutylene.

[0063] According to one embodiment of the present invention, the rare earth element ions can be selected from La 3+ 、Ce 3+ 、Sm 3+ 、Eu 3+ , Gd 3+ , Tb 3 + 、Dy 3+ , Y 3+ At least one of; preferably Ce 3+ 、Sm 3+ 、Eu 3+ , Gd 3+ , Tb 3+ 、Dy 3+ At least one of; More preferably Sm 3 + 、Eu 3+ , Tb 3+ 、Dy 3+ At least one of .

[0064] According to one embodiment of the present invention, the carboxylic acid rare earth complex is obtained by reacting the carboxylic acid represented by formula (I) and a rare earth-containing compound.

[0065] The molar ratio of the carboxylic acid represented by formula (I) to the rare earth element in the rare earth compound can be 1:(1-6); preferably 1:(1-5); more preferably 1:(2-5).

[0066] The compound of the rare earth element can be selected from at least one of the oxides of the rare earth element and the inorganic salts of the rare earth element; preferably at least one of the nitrates, sulfates, phosphates, acetates, carbonates, halides and oxides of the rare earth element; more preferably at least one of the nitrates, acetates, halides and oxides of the rare earth element. The inorganic salt of the rare earth element of the present invention can be either an anhydrous salt or a hydrated salt.

[0067] Reasonable carboxylic acid structure and reasonable ratio of carboxylic acid to rare earth elements are more conducive to the formation of structurally stable carboxylic acid rare earth complexes.

[0068] <Preparation method of carboxylic acid rare earth complex>

[0069] The present invention also provides a method for preparing the carboxylic acid rare earth complex as described above, comprising reacting the carboxylic acid represented by formula (I) with a compound of a rare earth element in a solvent and under acidic conditions to obtain the carboxylic acid rare earth complex. The method also comprises the steps of preparing the carboxylic acid represented by formula (I). The method is described in detail below.

[0070] According to one embodiment of the present invention, the solvent includes solvent A and solvent B.

[0071] Solvent A can be selected from at least one of acetonitrile, tetrahydrofuran, dimethylformamide, dimethylacetamide, and dimethyl sulfoxide; preferably at least one of tetrahydrofuran, dimethylformamide, dimethylacetamide, and dimethyl sulfoxide; more preferably at least one of tetrahydrofuran, dimethylformamide, and dimethylacetamide.

[0072] Solvent B can be selected from at least one of water and C1-C5 alkyl alcohols; preferably water and at least one of C1-C3 alkyl alcohols; more preferably water and at least one of C1-C3 n-alkyl alcohols. Examples of C1-C5 alkyl alcohols include, but are not limited to, methanol, ethanol, isopropanol, n-butanol, 1-pentanol, and 2-pentanol.

[0073] The volume ratio of solvent A to solvent B may be (1-5):1, preferably (1-3):1, and more preferably (1.5-3):1.

[0074] According to one embodiment of the present invention, the molar ratio of the rare earth element in the compound of the carboxylic acid represented by formula (I) and the rare earth element can be 1:(1-6); preferably 1:(1-5); more preferably 1:(2-5).

[0075] According to one embodiment of the present invention, the reaction temperature may be 80 to 150°C; preferably 90 to 140°C; more preferably 95 to 140°C.

[0076] According to another embodiment of the present invention, the reaction time may be 1 to 12 hours, preferably 2 to 10 hours, and more preferably 3 to 10 hours.

[0077] The reaction can be carried out in any high-temperature reaction equipment known in the art, preferably in a high-temperature reaction kettle containing a polytetrafluoroethylene liner.

[0078] In the present invention, the pH value of the acidic condition can be 1 to 6; preferably 2 to 6; more preferably 3 to 5. The present invention can use any type of acid solution to adjust the pH value, and is not particularly limited here. For example, it can be selected from at least one of hydrochloric acid solution, nitric acid solution, acetic acid solution, phosphoric acid solution, sulfuric acid solution, and carbonic acid solution; preferably at least one of hydrochloric acid solution, nitric acid solution, and sulfuric acid solution; more preferably at least one of hydrochloric acid solution with a concentration of 0.1 to 2 mol / L, nitric acid solution with a concentration of 0.1 to 2 mol / L, and sulfuric acid solution with a concentration of 0.1 to 2 mol / L.

[0079] According to one embodiment of the present invention, the method for preparing the carboxylic acid represented by formula (I) comprises the steps of preparing an intermediate product A, preparing an intermediate product B, preparing an intermediate product C and preparing a carboxylic acid, which are described in detail below.

[0080] Preparation steps of intermediate product A

[0081] Add titanium chloride, a reducing agent, and a compound represented by formula (II) into a first solvent and mix them to cause the compound represented by formula (II) to undergo a McMurry coupling reaction to obtain an intermediate product A;

[0082]

[0083] In formula (II), R1 and R2 can be independently selected from hydrogen or C1-C6 alkyl, preferably hydrogen or C1-C3 alkyl, more preferably hydrogen or C1-C3 n-alkyl. R5 and R6 can be independently selected from C1-C6 alkyl, preferably C1-C3 alkyl, more preferably C1-C3 n-alkyl.

[0084] The C1-C6 alkyl group may include, but is not limited to, methyl, ethyl, propyl, isopropyl, butyl, isobutyl, sec-butyl, tert-butyl, pentyl, methylbutyl, ethylpropyl, hexyl, methylpentyl, dimethylbutyl, ethylbutylene, and the like.

[0085] The first solvent can be selected from at least one of acetonitrile, tetrahydrofuran, dimethylformamide, dimethylacetamide, and dimethyl sulfoxide; preferably at least one of tetrahydrofuran, dimethylformamide, dimethylacetamide, and dimethyl sulfoxide; more preferably at least one of tetrahydrofuran and dimethyl sulfoxide.

[0086] According to one embodiment of the present invention, the titanium chloride may be selected from at least one of TiCl3 (titanium trichloride) and TiCl4 (titanium trichloride); preferably TiCl3 or TiCl4.

[0087] The reducing agent can be selected from at least one of Li (lithium), Na (sodium), K (potassium), Zn (zinc), Mg (magnesium), Al (aluminum), Pd (palladium), platinum (Pt), and LiAlH4 (lithium aluminum hydride); preferably at least one of Li, K, Zn, Mg, Al, Pd, and LiAlH4; more preferably at least one of K, Zn, Mg, and LiAlH4.

[0088] In the present invention, based on 1 g of the compound represented by formula (II), the amount of titanium chloride used can be 0.1 to 0.5 mL; preferably 0.15 to 0.45 mL; more preferably 0.2 to 0.4 mL.

[0089] Based on 1 mL of titanium chloride, the amount of the reducing agent used can be 0.5 to 5 g, preferably 1 to 5 g, and more preferably 1 to 4 g.

[0090] In the present invention, the McMurry coupling reaction is carried out under heating conditions, and the reaction can be heated to reflux. The reaction temperature can be 50 to 200°C, preferably 50 to 180°C, and more preferably 60 to 150°C.

[0091] The reaction time may be 12 to 48 hours, preferably 12 to 36 hours, and more preferably 24 to 36 hours.

[0092] In the present invention, the McMurry coupling reaction is carried out in a protective gas. The protective gas can be selected from at least one of nitrogen (N2) and an inert gas, and the inert gas includes helium (He), neon (Ne), argon (Ar), krypton (Kr), and xenon (Xe); preferably, the protective gas is selected from at least one of nitrogen, helium, neon, and argon; more preferably, the protective gas is selected from at least one of nitrogen, helium, and argon.

[0093] According to a preferred embodiment of the present invention, the first solvent can be added to the container under protective gas and stirred for 1 to 10 minutes, preferably 1 to 8 minutes, and more preferably 2 to 8 minutes. Then add the reducing agent and cool to -10 to 5°C, preferably -5 to 5°C, and more preferably -5 to 0°C. Then add titanium chloride and heat to temperature a, and stir at temperature a. Temperature a can be 10 to 30°C, preferably 15 to 30°C, and more preferably 20 to 30°C. The stirring time can be 0.1 to 5h, preferably 0.1 to 3h, and more preferably 0.2 to 2h. Then continue to heat to reflux and stir under reflux. The stirring time can be 0.1 to 5h, preferably 0.1 to 3h, and more preferably 0.2 to 2h. After stirring, cool the mixture again to -10 to 5°C, preferably -5 to 5°C, and more preferably -5 to 0°C. Then add the compound shown in formula (II), heat to reflux, and perform McMurry coupling reaction under reflux to generate a precipitate. After the reaction is completed, an aqueous solution of an alkali metal carbonate or an aqueous solution of an alkali metal bicarbonate is added to quench the reaction, and then the precipitate is filtered and recrystallized in a first recrystallization solvent to obtain an intermediate product A.

[0094] The alkali metal carbonate is preferably at least one of Li, Na, and K carbonates; more preferably at least one of Na2CO3 and K2CO3.

[0095] The alkali metal bicarbonate is preferably at least one of Li, Na, and K bicarbonates; more preferably at least one of NaHCO3 and KHCO3.

[0096] The mass concentration of the aqueous solution of alkali metal carbonate or the aqueous solution of alkali metal bicarbonate can be 1 to 20 wt %, preferably 2 to 18 wt %, and more preferably 5 to 15 wt %.

[0097] The first recrystallization solvent includes a first recrystallization solvent A and a first recrystallization solvent B. The first recrystallization solvent A can be selected from at least one of chloroalkanes; preferably at least one of dichloromethane, chloroform, and carbon tetrachloride; more preferably dichloromethane or chloroform. The first recrystallization solvent B is selected from at least one of C1-C5 alkyl alcohols; preferably at least one of C1-C3 alkyl alcohols; more preferably methanol or ethanol.

[0098] The volume ratio of the first recrystallization solvent A to the first recrystallization solvent B may be 1:(0.2-5), preferably 1:(0.5-5), and more preferably 1:(1-3).

[0099] Limiting the reaction conditions to the above range is conducive to the formation of intermediate product A and improves the yield of intermediate product A.

[0100] Preparation steps of intermediate product B

[0101] The intermediate product A and the boron halide are added into the second solvent for reaction to obtain the intermediate product B.

[0102] According to one embodiment of the present invention, the second solvent may be selected from at least one of halogenated alkanes; preferably at least one of chloroalkanes; more preferably at least one of dichloromethane, chloroform and carbon tetrachloride.

[0103] The boron halide can be selected from at least one of BF3, BBr3, BCl3, and BI3; preferably at least one of BBr3 and BCl3; more preferably BBr3 or BCl3.

[0104] In the present invention, based on 1 g of the intermediate product A, the amount of the boron halide used can be 0.1 to 5 mL; preferably 0.2 to 4 mL; more preferably 0.5 to 2 mL.

[0105] Based on 1 g of the intermediate product A, the amount of the second solvent used can be 5 to 100 mL, preferably 10 to 80 mL, and more preferably 10 to 60 mL.

[0106] In the present invention, the reaction temperature for obtaining the intermediate product B may be 10 to 50° C., preferably 15 to 45° C., and more preferably 20 to 40° C. The reaction time for obtaining the intermediate product B may be 5 to 24 hours, preferably 10 to 24 hours, and more preferably 12 to 20 hours.

[0107] According to a preferred embodiment of the present invention, the second solvent and the intermediate product A can be added to a container at -10 to 5°C, preferably -5 to 5°C, and more preferably -5 to 0°C, followed by stirring for 1 to 5 hours, preferably 1 to 3 hours, and more preferably 2 to 3 hours. Then the temperature is raised to the temperature of the reaction to obtain the intermediate product B, and the reaction is stirred at this temperature to generate a precipitate. After the reaction is completed, water is added at -10 to 5°C, preferably -5 to 5°C, and more preferably -5 to 0°C for quenching, and then the precipitate is filtered and washed. The precipitate is then recrystallized in the second recrystallization solvent to obtain an intermediate product B.

[0108] In the present invention, the water used for quenching can be selected from at least one of deionized water and ultrapure water; preferably deionized water.

[0109] In the present invention, the water used for washing can be selected from at least one of deionized water and ultrapure water, preferably deionized water. The washing times can be 1 to 5 times, preferably 2 to 5 times, and more preferably 2 to 4 times.

[0110] The second recrystallization solvent includes a second recrystallization solvent A and a second recrystallization solvent B. The second recrystallization solvent A can be selected from at least one of chloroalkanes; preferably at least one of dichloromethane, chloroform, and carbon tetrachloride; more preferably dichloromethane or chloroform. The second recrystallization solvent B is water. The water used can be selected from at least one of deionized water and ultrapure water; preferably deionized water.

[0111] The volume ratio of the second recrystallization solvent A to the second recrystallization solvent B may be 1:(0.2-5), preferably 1:(0.5-5), and more preferably 1:(1-3).

[0112] Limiting the reaction conditions to the above range is conducive to the formation of intermediate product B and improves the yield of intermediate product B.

[0113] Preparation steps of intermediate product C

[0114] Adding an alkali metal alkoxide to a third solvent for a first reaction; then adding the intermediate product B for a second reaction; then adding a compound represented by formula (III) for a third reaction to obtain an intermediate product C;

[0115]

[0116] In formula (III), R3 and R4 can be independently selected from hydrogen or C1-C6 alkyl; preferably hydrogen or C1-C3 alkyl; more preferably hydrogen or C1-C3 n-alkyl. R7 can be selected from C1-C6 alkyl; preferably C1-C3 alkyl; more preferably C1-C3 n-alkyl. X1 is halogen; preferably one of F, Cl, Br, I; more preferably Cl or Br.

[0117] In the present invention, the alkyl group may include but is not limited to methyl, ethyl, propyl, isopropyl, butyl, isobutyl, sec-butyl, tert-butyl, pentyl, methylbutyl, ethylpropyl, hexyl, methylpentyl, dimethylbutyl, ethylbutylene, heptyl and octyl.

[0118] The third solvent is selected from at least one of acetonitrile, tetrahydrofuran, dimethylformamide, dimethylacetamide, and dimethyl sulfoxide; preferably at least one of tetrahydrofuran, dimethylformamide, and dimethyl sulfoxide; more preferably at least one of tetrahydrofuran and dimethyl sulfoxide.

[0119] According to one embodiment of the present invention, the alkali metal alkoxide can be selected from at least one of the C1-C5 alkyl alkoxides of Li, Na, and K; preferably at least one of the C1-C3 alkyl alkoxides of Li, Na, and K; more preferably at least one of the C1-C3 alkyl alkoxides of Na and K; most preferably sodium tert-butoxide or potassium tert-butoxide.

[0120] In the present invention, based on 1 g of the intermediate product B, the amount of the alkali metal alkoxide used can be 0.1 to 1 g; preferably 0.2 to 0.8 g; more preferably 0.2 to 0.6 g.

[0121] Based on 1 g of the intermediate product B, the amount of the second solvent used can be 1 to 50 mL, preferably 5 to 30 mL, and more preferably 10 to 30 mL.

[0122] According to one embodiment of the present invention, the temperature of the first reaction may be 10-50° C., preferably 20-50° C., more preferably 30-45° C. The time of the first reaction may be 0.1-5 h, preferably 0.2-3 h, more preferably 0.5-2 h.

[0123] The temperature of the second reaction may be 10 to 80° C., preferably 20 to 60° C., and more preferably 30 to 60° C. The time of the second reaction may be 0.1 to 5 h, preferably 0.2 to 3 h, and more preferably 0.5 to 2 h.

[0124] The temperature of the third reaction may be 30 to 90° C., preferably 35 to 85° C., and more preferably 40 to 80° C. The time of the third reaction may be 2 to 12 h, preferably 3 to 10 h, and more preferably 5 to 10 h.

[0125] In the present invention, after the reaction is completed, water can be used to quench the reaction, and the water used for quenching can be selected from at least one of deionized water and ultrapure water; preferably deionized water.

[0126] According to a preferred embodiment of the present invention, the reaction product can be extracted after the quenching reaction. The extractant used can be selected from at least one of chloroalkanes; preferably at least one of dichloromethane, chloroform, and carbon tetrachloride; more preferably dichloromethane or chloroform.

[0127] According to a preferred embodiment of the present invention, after the extraction is completed, the extract is evaporated to remove the extractant to obtain an extract product. The extract product is recrystallized in a third recrystallization solvent to obtain an intermediate product C.

[0128] The third recrystallization solvent includes a third recrystallization solvent A and a third recrystallization solvent B. The third recrystallization solvent A can be selected from at least one of chloroalkanes; preferably at least one of dichloromethane, chloroform, and carbon tetrachloride; more preferably dichloromethane or chloroform. The third recrystallization solvent B can be selected from at least one of C1-C5 alkyl alcohols; preferably at least one of C1-C3 alkyl alcohols; more preferably methanol or ethanol.

[0129] The volume ratio of the third recrystallization solvent A to the third recrystallization solvent B may be 1:(0.2-5), preferably 1:(0.5-5), and more preferably 1:(1-3).

[0130] In the present invention, the step of preparing the intermediate product C is carried out in a protective gas. The protective gas can be selected from at least one of nitrogen (N2) and an inert gas, and the inert gas includes helium (He), neon (Ne), argon (Ar), krypton (Kr), and xenon (Xe); preferably, the protective gas is selected from at least one of nitrogen, helium, neon, and argon; more preferably, the protective gas is selected from at least one of nitrogen, helium, and argon.

[0131] Limiting the reaction conditions to the above range is conducive to the formation of intermediate product C and improves the yield of intermediate product C.

[0132] Carboxylic acid preparation steps

[0133] Alkali metal hydroxide and intermediate product C are added to a fourth solvent for reaction. After the reaction, the organic solvent is removed and an acid is added to obtain a carboxylic acid represented by formula (I).

[0134] According to one embodiment of the present invention, the fourth solvent includes solvent C, solvent D and solvent E. Solvent C is selected from at least one of acetonitrile, tetrahydrofuran, dimethylformamide, dimethylacetamide and dimethyl sulfoxide; preferably at least one of tetrahydrofuran, dimethylformamide and dimethyl sulfoxide; more preferably at least one of tetrahydrofuran and dimethyl sulfoxide. The solvent D is selected from at least one of C1 to C5 alkyl alcohols; preferably at least one of C1 to C3 alkyl alcohols; more preferably methanol or ethanol. The solvent E is water; preferably deionized water or ultrapure water.

[0135] The volume ratio of solvent C, solvent D and solvent E may be (1-5):(1-5):1, preferably (1-4):(1-4):1, and more preferably (2-4):(2-4):1.

[0136] The alkali metal hydroxide in the present invention can be selected from at least one of LiOH, NaOH, and KOH; preferably at least one of NaOH and KOH; more preferably NaOH or KOH.

[0137] In the present invention, based on 1 g of the intermediate product C, the amount of the alkali metal hydroxide used can be 0.1 to 1 g, preferably 0.2 to 0.8 g, and more preferably 0.3 to 0.8 g.

[0138] Based on 1 g of the intermediate product C, the amount of the fourth solvent used can be 5 to 100 mL, preferably 10 to 80 mL, and more preferably 10 to 70 mL.

[0139] According to one embodiment of the present invention, the reaction is carried out under heating reflux. The reaction time may be 1 to 12 hours, preferably 2 to 10 hours, and more preferably 3 to 8 hours.

[0140] According to one embodiment of the present invention, after the reaction is completed, the organic solvent is removed, and an acid is added to the remaining aqueous phase to obtain a precipitate. The precipitate is filtered, washed, and dried to obtain the carboxylic acid represented by formula (I).

[0141] In the present invention, the added acid can be selected from at least one of hydrochloric acid solution, nitric acid solution, phosphoric acid solution, and sulfuric acid solution; preferably at least one of hydrochloric acid solution, nitric acid solution, and sulfuric acid solution; more preferably at least one of a hydrochloric acid solution with a concentration of 10 to 12 mol / L, a nitric acid solution with a concentration of 8 to 12 mol / L, and a sulfuric acid solution with a concentration of 10 to 20 mol / L.

[0142] The filtering, washing and drying in the present invention are all achieved by any known method in the art, and are not particularly limited here. The water used for washing is preferably deionized water.

[0143] Limiting the reaction conditions to the above range is conducive to the formation of carboxylic acid rare earth complexes and improving the yield of carboxylic acid rare earth complexes.

[0144] <Composite Materials>

[0145] The present invention also provides a composite material, which is formed by coating the carboxylic acid rare earth complex on the surface of silicon dioxide via a silane coupling agent.

[0146] According to one embodiment of the present invention, the silane coupling agent is selected from at least one of N-(β-aminoethyl-γ-aminopropyl)methyldimethoxysilane, N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane, γ-aminopropyltriethoxysilane, γ-aminopropyltrimethoxysilane, vinyltrimethoxysilane, γ-(2,3-epoxypropoxy)propyltrimethoxysilane, γ-(methacryloyloxy)propyltrimethoxysilane and γ-mercaptopropyltriethoxysilane; preferably N-(β-aminoethyl-γ-aminopropyl)methyldimethoxysilane, γ-aminopropyltrimethoxysilane, γ-aminopropyltriethoxysilane, γ-(2,3-epoxypropoxy)propyltrimethoxysilane, γ-(methacryloyloxy)propyltrimethoxysilane, γ-mercaptopropyltriethoxysilane. At least one of N-(β-aminoethyl-γ-aminopropyl)methyldimethoxysilane, N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane, γ-aminopropyltriethoxysilane, γ-aminopropyltrimethoxysilane, vinyltrimethoxysilane, and γ-(methacryloyloxy)propyltrimethoxysilane; more preferably at least one of N-(β-aminoethyl-γ-aminopropyl)methyldimethoxysilane, N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane, γ-aminopropyltriethoxysilane, and γ-aminopropyltrimethoxysilane.

[0147] In the present invention, the carboxylic acid rare earth complex is coated on the surface of silicon dioxide through a silane coupling agent, so that the obtained composite material is not easy to agglomerate and has better dispersibility and stability.

[0148] <Method for preparing composite material>

[0149] The present invention also provides a method for preparing the composite material as described above, comprising a step of activating silicon dioxide, a step of coating with a silane coupling agent, and a step of coating with a carboxylic acid rare earth complex, which is described in detail below.

[0150] Silica Activation Steps

[0151] The silica is immersed in a weak alkaline aqueous solution and allowed to stand for 1 to 12 hours, and then filtered, washed and dried.

[0152] According to one embodiment of the present invention, the weak alkaline aqueous solution can be selected from at least one of ammonia water, an alkali metal carbonate aqueous solution, and an alkali metal bicarbonate aqueous solution; preferably at least one of ammonia water, a sodium carbonate aqueous solution, a sodium bicarbonate aqueous solution, a potassium carbonate aqueous solution, and a potassium bicarbonate aqueous solution; more preferably at least one of ammonia water, a sodium carbonate aqueous solution, and a potassium carbonate aqueous solution.

[0153] The standing time may be 1 to 12 hours, preferably 2 to 10 hours, and more preferably 3 to 9 hours.

[0154] The filtering, washing and drying in the present invention can be achieved by any known method in the art, and are not particularly limited here. The water used for washing is preferably deionized.

[0155] Reasonable activation conditions are conducive to activating the hydroxyl groups on the SiO2 surface and improving the bonding ability between SiO2 and silane coupling agents.

[0156] Silane coupling agent coating steps

[0157] The dried silicon dioxide and the silane coupling agent are placed in C1-C5 alkyl alcohol and reacted at 50-120° C. to obtain silicon dioxide with the surface coated by the silane coupling agent.

[0158] According to one embodiment of the present invention, the C1-C5 alkyl alcohol may be a C1-C3 alkyl alcohol; preferably a C1-C3 normal alkyl alcohol; more preferably methanol or ethanol.

[0159] According to one embodiment of the present invention, based on 1g of silicon dioxide, the amount of the silane coupling agent used may be 1 to 10g; preferably 1 to 8g; more preferably 2 to 8g.

[0160] Based on 1 g of silica coated with a silane coupling agent, the amount of C1-C5 alkyl alcohol used may be 1-10 mL, preferably 1-8 mL, and more preferably 2-6 mL.

[0161] According to one embodiment of the present invention, the reaction temperature may be 50 to 120°C; preferably 60 to 110°C; more preferably 65 to 100°C.

[0162] The reaction time may be 1 to 20 hours, preferably 2 to 18 hours, and more preferably 3 to 15 hours.

[0163] According to a preferred embodiment of the present invention, the prepared silicon dioxide coated with the silane coupling agent can also be filtered, washed and dried.

[0164] Filtration, washing and drying can be achieved by any known method in the art, and are not particularly limited herein. The water used for washing is preferably deionized water.

[0165] Limiting the reaction conditions to the above range is conducive to the stable combination of the silane coupling agent and the silica, thereby generating silica coated with the silane coupling agent with a stable structure.

[0166] Carboxylate rare earth complex coating step

[0167] The silicon dioxide with the surface coated by the silane coupling agent and the carboxylic acid rare earth complex are placed in C1-C5 alkyl alcohol and reacted at 50-120 DEG C to prepare the composite material.

[0168] According to one embodiment of the present invention, the pH value for the reaction may be 6 to 8, preferably 6.5 to 7.5, and more preferably 7. The present invention may use any alkaline solution to adjust the pH value, such as but not limited to at least one of ammonia water, alkali metal hydroxide solution, and alkali gold carbonate solution; preferably at least one of ammonia water, sodium hydroxide aqueous solution, and sodium carbonate aqueous solution; more preferably ammonia water.

[0169] According to one embodiment of the present invention, based on 1g of silicon dioxide coated with a silane coupling agent, the amount of the carboxylic acid rare earth complex used may be 1 to 5g; preferably 1 to 4g; more preferably 1.5 to 3.5g.

[0170] Based on 1 g of silica coated with a silane coupling agent, the amount of C1-C5 alkyl alcohol used may be 1-10 mL, preferably 2-10 mL, and more preferably 2-8 mL.

[0171] The C1-C5 alkyl alcohol may be a C1-C3 alkyl alcohol; preferably a C1-C3 normal alkyl alcohol; more preferably methanol or ethanol.

[0172] According to one embodiment of the present invention, the reaction temperature may be 50 to 120°C; preferably 60 to 110°C; more preferably 65 to 100°C.

[0173] The reaction time may be 1 to 20 hours, preferably 2 to 18 hours, and more preferably 3 to 15 hours.

[0174] Limiting the reaction conditions to the above range is conducive to the stable combination of silicon dioxide coated with silane coupling agent and carboxylic acid rare earth complex to form a composite material; it can ensure that the prepared composite material has good stability and recyclability, and is more conducive to improving the sensitivity of the composite material to polychlorinated biphenyl detection.

[0175] The raw materials used in the present invention can be commercially available products or prepared by existing preparation methods, and are not particularly limited here. The purity of the raw materials of the present invention is at least industrial purity (99.9wt%).

[0176] <Purpose>

[0177] The invention also provides use of the composite material in detecting polychlorinated biphenyls.

[0178] According to a preferred embodiment of the present invention, the composite material can be used to detect polychlorinated biphenyls in water.

[0179] According to one embodiment of the present invention, the detection limit of the composite material for polychlorinated biphenyls is at most 8 μM, preferably at most 7 μM, and more preferably at most 6.8 μM.

[0180] According to one embodiment of the present invention, the polychlorinated biphenyls may be at least one of tri- to decachlorobiphenyls; preferably at least one of tri- to octachlorobiphenyls; more preferably at least one of tri- to hexachlorobiphenyls; further preferably at least one of 2,2',5-trichlorobiphenyl, 2,2',5,5'-tetrachlorobiphenyl, and 2,2',4,4',5,5'-hexachlorobiphenyl.

[0181] <Test Method>

[0182] Fluorescence excitation and emission spectra were measured using a Horiba FL-3 fluorescence spectrometer.

[0183] Infrared spectroscopic determination: Thermo Fisher Scientific Nicolet iS20 infrared spectrometer was used for detection.

[0184] X-ray photoelectron spectroscopy (XPS) was performed using a Thermo Scientific ESCALAB QXi X-ray photoelectron spectrometer.

[0185] Transmission electron microscopy (TEM) determination: Thermo Fisher Talos F200i from the United States was used for detection.

[0186] <Ingredients>

[0187] The raw materials in the following examples are all commercially available products unless otherwise specified.

[0188] Among them, europium oxide, 4,4'-dimethylbenzophenone, tetrakis(4-methoxyphenyl), methyl 4-(bromomethyl)benzoate, potassium hydroxide, tetrahydrofuran, and dichloromethane were purchased from Shanghai Aladdin Reagent Co., Ltd. Hydrochloric acid was purchased from Fuchen Chemical Reagent Co., Ltd. The remaining drugs were purchased from McLean Biochemical Technology Co., Ltd.

[0189] Preparation Example 1

[0190] Preparation of tetrakis-(4-carboxy-1-methyleneoxy-(1,1-biphenyl))ethylene (H4L), the preparation route is as follows Figure 1 shown.

[0191] Under nitrogen (N2) protection, 40 mL of tetrahydrofuran (THF) was added to the container and stirred at room temperature for 5 min, then 6.5 g of zinc powder was added, and 5.5 mL of titanium tetrachloride was slowly added with a syringe after cooling to 0 ° C to form a suspension. The suspension was heated to room temperature (same as at 25 ° C), stirred at room temperature for 0.5 h, then heated to reflux and stirred for 1.5 h. Then the system was cooled to 0 ° C again. 20 g of 4,4'-dimethoxybenzophenone was added and reacted under reflux for 24 h. After the reaction was completed, 50 mL of a 10 wt% K2CO3 aqueous solution was added to quench the reaction, the precipitate generated by the reaction was filtered, and the precipitate was recrystallized in 20 mL of a methanol solution of dichloromethane (the volume ratio of CH2Cl2 to CH3OH was 1:1) to obtain a light yellow crystal, which was the intermediate product A (tetrakis (4-methoxyphenyl) ethylene), with a yield of 63 wt%.

[0192] At 0°C, 5 g of intermediate product A and 100 mL of anhydrous dichloromethane (DCM) were added to the container, 4.2 mL of BBr3 was added by syringe, and stirred at 0°C for 2 h to form a mixture. The mixture was then stirred at room temperature for 16 h to generate a precipitate. 100 mL of deionized water was then added at -5°C to quench the reaction. The generated precipitate was filtered and rinsed with deionized water. The rinsed precipitate was recrystallized in 20 mL of an ethanol aqueous solution (the volume ratio of CH3CH2OH to H2O was 1:1) to obtain a pink solid, which was intermediate product B (methyl 4-(bromomethyl)benzoate), with a yield of 47 wt%.

[0193] Under nitrogen protection, 1.83g of potassium tert-butoxide (KTB) and 50mL of dimethyl sulfoxide (DMSO) were added to a container, reacted at 35°C for 0.5h, then 5g of intermediate product B was added, the reaction continued at 45°C for 0.5h, and then 14.5g of methyl 4-(bromomethyl)benzoate was added, and the reaction was further reacted at 60°C for 8h. Then 100mL of deionized water was added to quench the reaction, and then the reaction product was extracted with dichloromethane three times, each time using 40mL of dichloromethane, and dichloromethane was evaporated after extraction. The reaction product obtained by extraction was recrystallized in 15mL of CH2Cl2 / CH3OH (V / V=1:2) solution to obtain light yellow crystals, which were intermediate product C, with a yield of 41%.

[0194] 3g of intermediate product C and 2.04g of potassium hydroxide were added to a container, and 35mL of tetrahydrofuran and ethanol aqueous solution (the volume ratio of THF, CH3CH2OH and H2O was 3:3:1) was added, heated to reflux, and reacted under reflux for 6h. After the reaction, the organic phase was separated and removed, and concentrated hydrochloric acid (concentration of 18.4mol / L) was added to the aqueous phase to adjust the pH value of the aqueous phase to 1 to generate a precipitate. The precipitate was filtered, washed, and dried to obtain a light pink product, namely tetrakis-(4-carboxyl-1-methyleneoxy-(1,1-biphenyl))ethylene (referred to as H4L), with a yield of 34wt%.

[0195] Example 1

[0196] Preparation of composite materials (SiO2@WD-53@L-Eu), the preparation route is as follows Figure 2 shown.

[0197] 5 mL of N,N-dimethylformamide and 3 mL of water were added to the inner lining of a polytetrafluoroethylene reactor, and then 0.01 mmol of H4L and 0.01 mmol of Eu2O3 were added, and the pH value of the reaction system was adjusted to 5 with a dilute nitric acid solution (concentration of 1 mol / L), and then reacted at 130°C for 8 h to obtain a carboxylate europium complex (denoted as L-Eu).

[0198] 5g of SiO2 powder was immersed in 0.1mol / L ammonia water and allowed to stand for 6h to activate the hydroxyl groups on the surface of SiO2. The activated SiO2 was filtered, washed, dried, and placed in a container. 10g of N-(β-aminoethyl-γ-aminopropyl)methyldimethoxysilane (WD-53) and 10mL of anhydrous ethanol were added. The reaction system was reacted at 80°C for 8h, filtered, washed, and dried to obtain SiO2 with a surface coated with a silane coupling agent (referred to as SiO2@WD-53).

[0199] 1 g SiO2@WD-53 was added to the container, and then 1.5 g L-Eu and 5 mL of anhydrous ethanol were added, and the pH value of the reaction system was adjusted to 7 with ammonia water (concentration of 0.1 mol / L), and then reacted at 80 °C for 12 h to obtain a composite material (denoted as SiO2@WD-53@L-Eu).

[0200] Experimental Example 1

[0201] By measuring the XPS spectrum of 30 mg of the composite material SiO2@WD-53@L-Eu prepared in Example 1, the chemical bonds in the composite material were further analyzed. The results are as follows: Figure 3 As shown. Figure 3 It can be seen that the peaks of Si2p, O1s, C1s, N1s, and Eu3d can be identified in the overall spectrum (a) of the composite material SiO2@WD-53@L-Eu, proving that the carboxylic acid europium complex L-Eu, the coupling agent WD-53 and SiO2 combine to form the composite material SiO2@WD-53@L-Eu. In the C1s energy spectrum (b), the binding energies of the bonds C-Si (284.1eV), CC / C=C (284.7eV), CN (285.3eV), CO (286.1eV), and C=O (288.5eV) can be observed. In the O1s energy spectrum (c), the three peaks of Si-O-Si (532.5eV), CO (532.5eV), and C=O (31.6eV) can be observed, which proves that the ligand is formed through the carboxylic acid and Eu. 3+ Coordination, coupling agent WD-53 is connected to SiO2 through Si-O-Si bond. In the Eu3d spectrum (d), Eu3d3 / 2 (1164.9eV), Eu3d5 / 2 (1135.4eV) and satellite peaks at 1156.6eV are observed, which further indicates that the europium element is in the form of Eu 3+ The XPS spectrum results prove that the composite material SiO2@WD-53@L-Eu is a composite material formed by coupling agent WD-53 and carboxylic acid europium complex L-Eu coated on SiO2.

[0202] In order to further understand the morphological characteristics of the composite material SiO2@WD-53@L-Eu prepared in Example 1, a TEM (transmission electron microscope) test was performed on it. The results are as follows: Figure 4 and 5 As shown. Figure 4 It can be clearly observed that the film formed by WD-53@L-Eu on the outer layer of SiO2 has a thickness of 11.07nm (d). Figure 5 It can be seen that the composite material SiO2@WD-53@L-Eu is a core-shell material, and the elements are evenly distributed.

[0203] The infrared spectra of 10 mg of H4L in Preparation Example 1, L-Eu in Example 1, SiO2, SiO2@WD-53 and the composite material SiO2@WD-53@L-Eu were detected respectively. The results are as follows: Figure 6 In the infrared spectrum of H4L, it can be observed that 3449.18cm -1 The broad absorption peak at 1640 cm-1 is the stretching vibration of -OH on the carboxyl group. -1 The stretching vibration of C=O is observed in the infrared spectrum of L-Eu. It can be observed that the stretching vibration absorption peak intensity of -OH on the carboxyl group is weakened from 1640 cm -1 Move to 3444.07cm -1 , C=O stretching vibration absorption from 1640.04cm -1 Move to 1634.33cm -1 , indicating that Eu 3+ Coordinated with carboxylic acid H4L. SiO2 infrared spectrum data showed 3660.84cm -1 The broad absorption peak at 1635.76 cm is the -OH stretching vibration. -1 He 814.31cm -1 The stretching vibration and bending vibration absorption peaks of Si-O-Si bonds can be seen in the infrared spectra of SiO2@WD-53 and SiO2@WD-53@L-Eu. The -OH stretching vibration on SiO2@WD-53 and SiO2@WD-53@L-Eu moves to 3663.69cm -1 and 3439.80cm -1 The stretching vibration absorption peak of Si-O-Si bond moves to 1612.94 cm -1 and 1624.34cm -1 The bending vibration absorption peak of Si-O-Si bond moves to 811.46 cm -1 and 807.18cm -1 This indicates that SiO2 is coated by WD-53 and L-Eu.

[0204] Experimental Example 2

[0205] 0.002 g of the composite material SiO2@WD-53@L-Eu prepared in Example 1 was dispersed in 2 mL of anhydrous ethanol and ultrasonically treated for 15 min to prepare a dispersion with a concentration of 1 mg / mL for use. 2,2',5-trichlorobiphenyl was weighed and dissolved in 1 mL of anhydrous ethanol to prepare a dispersion with a concentration of 1×10 -2 mol·L -1The 2,2',5-trichlorobiphenyl solution was prepared in the same way. The 2,2',5,5'-tetrachlorobiphenyl and 2,2',4,4',5,5'-hexachlorobiphenyl solutions of the same concentration were prepared. Different volumes of the above 2,2',5-trichlorobiphenyl solution were added to the dispersion of the composite material SiO2@WD-53@L-Eu, and the fluorescence emission spectrum of the dispersion was detected. The results are shown in Figure 7 As shown. As the content of 2,2',5-trichlorobiphenyl in the dispersion gradually increases, the fluorescence emission intensity of SiO2@WD-53@L-Eu slowly decreases. When the volume of 2,2',5-trichlorobiphenyl added to the dispersion reaches 500μL, the fluorescence emission spectrum of SiO2@WD-53@L-Eu is almost completely quenched. The same method was used to detect the fluorescence quenching of the dispersion of the composite material SiO2@WD-53@L-Eu by 2,2',5,5'-tetrachlorobiphenyl solution and 2,2',4,4',5,5'-hexachlorobiphenyl solution. The results are shown as follows. Figure 8 and Fig. 9 The fluorescence quenching constants of 2,2',5-trichlorobiphenyl, 2,2',5,5'-tetrachlorobiphenyl and 2,2',4,4',5,5'-hexachlorobiphenyl were obtained by fitting to be 4.446×10 3 M -1 ,4.819×10 3 M -1 ,5.261×10 3 M -1 The detection limits of the three were further calculated to be 6.748μM, 6.225μM, and 5.752μM, respectively.

[0206] Experimental Example 3

[0207] Take 500 μL of the dispersion of the composite material SiO2@WD-53@L-Eu prepared in Experimental Example 2 with a concentration of 1 mg / mL, and detect its fluorescence spectrum. Then add 2,2',5-trichlorobiphenyl solution to quench the fluorescence of the composite material, detect the fluorescence spectrum of the solution again, and then wash the composite material SiO2@WD-53@L-Eu with anhydrous ethanol. Repeat the above fluorescence quenching experiment four times, and compare the fluorescence intensity of the fluorescence spectra of the five quenching experiments at the emission wavelength of 616 nm. The results are as follows: Fig.10 As shown. Compared with before the experiment, although the fluorescence intensity of the dispersion of the composite material SiO2@WD-53@L-Eu decreased by 19% after three fluorescence quenching experiments, the fluorescence quenching efficiency of the fourth experiment can still reach 89%. This fully demonstrates that the composite material SiO2@WD-53@L-Eu of the present invention has good recyclability when detecting polychlorinated biphenyls in the solution.

[0208] The present invention is not limited to the above-mentioned embodiments. Without departing from the essential content of the present invention, any deformation, improvement and substitution that can be conceived by those skilled in the art shall fall within the scope of the present invention.

Claims

1. A carboxylic acid rare earth complex, characterized in that: The carboxylic acid rare earth complex is formed by complexing carboxylic acid with rare earth element ions; wherein, The carboxylic acid has a structure as shown in formula (I): Wherein, R1, R2, R3, and R4 are independently selected from hydrogen or a C1-C6 alkyl group.

2. The carboxylic acid rare earth complex according to claim 1, characterized in that The rare earth element ion is selected from La 3+ 、Ce 3+ 、Sm 3+ 、Eu 3+ , Gd 3+ , Tb 3+ 、Dy 3+ , Y 3+ At least one of .

3. The carboxylic acid rare earth complex according to claim 1, characterized in that The carboxylic acid rare earth complex is obtained by reacting the carboxylic acid shown in formula (I) with a compound containing a rare earth element; wherein the molar ratio of the carboxylic acid shown in formula (I) to the rare earth element in the compound containing the rare earth element is 1:(1-6).

4. A method for preparing the carboxylic acid rare earth complex according to any one of claims 1 to 3, comprising the following steps: The carboxylic acid represented by formula (I) is reacted with a compound containing a rare earth element in a solvent under acidic conditions to obtain a carboxylic acid rare earth complex; Wherein, the compound containing rare earth elements is selected from at least one of oxides of rare earth elements and inorganic salts of rare earth elements; The solvent includes solvent A and solvent B; the solvent A is selected from at least one of acetonitrile, tetrahydrofuran, dimethylformamide, dimethylacetamide, and dimethyl sulfoxide; the solvent B is selected from at least one of water and C1-C5 alkyl alcohol; The reaction temperature is 80-150°C.

5. The preparation method according to claim 4, characterized in that: The preparation method of the carboxylic acid represented by formula (I) comprises the following steps: 1) adding titanium chloride, a reducing agent, and a compound represented by formula (II) into a first solvent and mixing them, so that the compound represented by formula (II) undergoes a McMurry coupling reaction to obtain an intermediate product A; Wherein, R1 and R2 are independently selected from hydrogen or C1-C6 alkyl; R5 and R6 are independently selected from C1-C6 alkyl; The first solvent is selected from at least one of acetonitrile, tetrahydrofuran, dimethylformamide, dimethylacetamide, and dimethyl sulfoxide; 2) adding the intermediate product A and the boron halide to the second solution, mixing and reacting to obtain the intermediate product B; The second solvent is selected from at least one of halogenated alkanes; 3) adding an alkali metal alkoxide to a third solvent for a first reaction; then adding the intermediate product B for a second reaction; then adding the compound represented by formula (III) for a third reaction to obtain an intermediate product C; Wherein, R3 and R4 are independently selected from hydrogen or C1-C6 alkyl; R7 is selected from C1-C6 alkyl; X1 is halogen; The third solvent is selected from at least one of acetonitrile, tetrahydrofuran, dimethylformamide, dimethylacetamide, and dimethyl sulfoxide; 4) adding an alkali metal hydroxide and the intermediate product C into a fourth solvent for reaction, removing the organic solvent after the reaction, and adding an acid to obtain a carboxylic acid represented by formula (I); The fourth solvent includes solvent C, solvent D and solvent E; the solvent C is selected from at least one of acetonitrile, tetrahydrofuran, dimethylformamide, dimethylacetamide, and dimethyl sulfoxide; the solvent D is selected from at least one of C1-C5 alkyl alcohols; and the solvent E is water.

6. A composite material, characterized in that: The composite material is formed by coating the carboxylic acid rare earth complex according to any one of claims 1 to 3 on the surface of silicon dioxide via a silane coupling agent.

7. The composite material according to claim 6, characterized in that The silane coupling agent is selected from at least one of N-(β-aminoethyl-γ-aminopropyl)methyldimethoxysilane, N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane, γ-aminopropyltriethoxysilane, γ-aminopropyltrimethoxysilane, vinyltrimethoxysilane, γ-(2,3-epoxypropyloxy)propyltrimethoxysilane, γ-(methacryloyloxy)propyltrimethoxysilane and γ-mercaptopropyltriethoxysilane.

8. A method for preparing the composite material according to claim 6 or 7, comprising the following steps: A) immersing the silicon dioxide in a weak alkaline aqueous solution and allowing it to stand for 1 to 12 hours, followed by filtering, washing and drying the silicon dioxide; wherein the weak alkaline aqueous solution is selected from at least one of aqueous ammonia, an aqueous solution of an alkali metal carbonate, and an aqueous solution of an alkali metal bicarbonate; B) placing the dried silica and silane coupling agent in step A) in a C1-C5 alkyl alcohol and reacting at 50-120° C. to obtain silica with the surface coated with the silane coupling agent; C) placing the silicon dioxide with the surface coated with a silane coupling agent obtained in step B) and the carboxylic acid rare earth complex according to any one of claims 1 to 3 in a C1 to C5 alkyl alcohol and reacting them at 50 to 120° C. to obtain a composite material.

9. The preparation method according to claim 8, characterized in that: In step C), the reaction is carried out at a pH value of 6 to 8.

10. Use of the composite material according to any one of claims 6 or 7 in detecting polychlorinated biphenyls.

Citation Information

Patent Citations

  • Europium complex silicon dioxide fluorescent nano particles and preparation method thereof

    CN101735216A

  • Lipophilic silicon dioxide-rare earth nano-fluorescent material and preparation method thereof

    CN106190103A

  • Construction of shining metal organic frame for Eu&lt;3+&gt; sensitization

    CN106432295A

  • Rare earth europium fluorescent chelating agent and preparation method thereof

    CN101735139A

  • Aromatic or aliphatic formic acid-rare earth complex molecular hybrid luminescent material and preparation method thereof

    CN102212361A

Cited By

  • Multi-layer composite pipe body with gradient self-repairing function and preparation method of multi-layer composite pipe body

    CN122210973A

  • Compound pipeline based on chemical bonding and stress buffering and application thereof

    CN122467563A